A Cross-Linked Polymer Soil Stabilizer for Hillslope Conservation on the Loess Plateau - Zhang, Xiaochao; Zhong, Yujian; Pei, Xiangjun; Duan, Yuying (Frontiers in Earth Science, 2021)
The soil of the Loess Plateau is highly susceptible to erosion due to its distinct loess structure with poor water stability and disintegrates easily. Previous research has focused on improving soil strength without considering stability and ecological performance. Comprehensive improvements may be achieved through the use of cross-linked polymers (CLPs), but their effect on loess structure remains unclear. In the present study, we investigate the use of CLPs as a new organic soil stabilizer to improve soil aggregate stability. To determine the effect of CLPs on the stabilization of loess, a series of indoor tests was conducted to assess unconfined compressive strength, water stability, soil-water characteristics, and plant height. The stabilization mechanism was analyzed by comparing the microstructure, mineral composition, and features of functional groups of loess before and after treatment. The results showed that, compared with untreated loess, the unconfined compressive strength and anti-disintegration property of treated loess were significantly increased. The water retention capacity was improved, and the germination rate and growth of plants were promoted. Microscopic analysis showed that the use of CLPs did form new minerals in the loess or change the functional groups, rather, CLPs improved the microstructure, reduced the total volume of pores, and increased the degree of soil compaction. Finally, the practical application of CLPs was studied through a field test. The results demonstrated that loess hillslope erosion was effectively controlled by CLPs. Under the same erosive conditions, the slope surface treated with CLPs was more intact than the untreated slope surface. Our findings provide new strategies regarding the application of CLPs as soil stabilizers to control loess erosion and promote vegetation restoration.